2018
DOI: 10.1093/advances/nmy022
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Nutrients in Human Milk

Abstract: The WHO recommends exclusive breastfeeding for the first 6 mo of life to promote optimal infant health and development. Understanding the micro- and macronutrient concentrations of human milk and how each nutrient fluctuates with lactational stage, maternal factors, and supplementation is imperative for supporting good breastfeeding practices. Where maternal undernutrition compromises human milk quality, a thorough awareness of the effectiveness of interventions can direct efforts to achieve both maternal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
280
2
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(293 citation statements)
references
References 271 publications
(347 reference statements)
6
280
2
5
Order By: Relevance
“…The concentration of some water-soluble vitamins, such as thiamin, vitamin B-6 and biotin, increases during the lactation period, while the riboflavin content remains constant. Vitamins A and E are present in high concentrations in colostrum compared to mature milk, while vitamins D and K remain in low quantity in human milk (Coryell et al, 1945;Dror and Allen, 2018). Maternal diet seems to notably influence the vitamin profile in breast milk, resulting, in some cases, in the necessity of dietary supplementation for the mother during the lactation period (Valentine and Wagner, 2013).…”
Section: Vitamins Ions and Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentration of some water-soluble vitamins, such as thiamin, vitamin B-6 and biotin, increases during the lactation period, while the riboflavin content remains constant. Vitamins A and E are present in high concentrations in colostrum compared to mature milk, while vitamins D and K remain in low quantity in human milk (Coryell et al, 1945;Dror and Allen, 2018). Maternal diet seems to notably influence the vitamin profile in breast milk, resulting, in some cases, in the necessity of dietary supplementation for the mother during the lactation period (Valentine and Wagner, 2013).…”
Section: Vitamins Ions and Metalsmentioning
confidence: 99%
“…Maternal diet seems to notably influence the vitamin profile in breast milk, resulting, in some cases, in the necessity of dietary supplementation for the mother during the lactation period (Valentine and Wagner, 2013). In contrast, other micronutrients, such as ions and mineral salts, show a constant bioavailability during the course of lactation, with the exception of zinc, copper and iron, which are present in high concentration immediately after childbirth, but decrease in the following months, and seem to be less influenced by maternal diet (Dror and Allen, 2018).…”
Section: Vitamins Ions and Metalsmentioning
confidence: 99%
“…Nevertheless, we may have missed some B12 food sources and therefore underestimated total B12 intake within food groups, which could explain the lack of association between B12 intake and milk concentration. In studies from low-income countries with a higher prevalence of deficient or marginal B12 status, maternal vitamin B12 intake was associated with human milk B12 concentrations at 1, 6, and 12 months postpartum in Kenya [27] and Guatemala [1,2,28].…”
Section: Discussionmentioning
confidence: 94%
“…Vitamin B12 (B12) is an essential micronutrient for normal growth and cognitive development in infants [1,2]. Infant B12 status depends on both sufficient transfer in utero and sufficient transfer through breast milk, both of which are strongly affected by maternal status [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…35,36 Folate binding protein (FBP) in breastmilk has a higher affinity for folic acid than reduced folate forms; after ingestion, folic acid may be less readily released by FBP as it passes through the gastrointestinal tract, reducing subsequent absorption and potentially impacting the infant's folate status. 33 Although total breastmilk folate concentrations are unaffected by maternal folate status (except in cases of severe deficiency) 34,37 , the proportion breastmilk folate as folic acid may be influenced. 33 In a recent retrospective cohort study (n=561), women who reported supplementing with >0.4 mg/day folic acid had proportionally higher UMFA in breastmilk than women who reported 6 supplementing with <0.4 mg/day (50% as compared to 25% respectively).…”
Section: Periconceptional Folate Requirementsmentioning
confidence: 99%